PEMANFAATAN HASIL KEBUN TANAMAN JAGUNG GUNA MEMBANGUN JIWA INTERPRENEUR IBU-IBU PKK BERBASIS POTENSI DI DESA MANGGIS KEC. MOJOSONGO KAB. BOYOLALI - Sulistri Anuria; Yosep Natan Nitit; Muryanto; Akhyari; Herdin Yudha Puspita; Sertar Mohammad Thohry Thohir; Sertar Dandi Prama Putra (JURNAL NAGARA BHAKTI, 2024)
In Indonesia, corn is one of the important agricultural commodities that is strategic in the future as a carbohydrate substitute for rice in food diversification efforts, so it is not surprising that corn is also a commodity chosen by the government to support the national food security program in 2023. Corn is one of the most important cereal crops in Indonesia. Apart from being a staple food crop to replace rice, corn also has the benefits of almost the entire tree, starting from the leaves for animal feed and compost. The corn fruit consists of the cob, kernels and cob, all three of which have economic benefits. Corn cob has long been used as raw material for feed, compost and the cigarette industry. As a food ingredient, corn kernels have nutritional content, namely Calories, Protein, Fat, Carbohydrates, Calcium, Phosphorus, Iron, Vitamin A, Vitamin B1. Other benefits of corn can reduce hypertension so that it can prevent heart disease. The heart can control diabetes, improve digestion, prevent constipation and hemorrhoids because corn is rich in fiber, and can even reduce the risk of colon cancer. Phosphorus is good for bone health, this nutrient not only prevents bones from cracking due to age, but also improves kidney function.( Director General of Food Crops Kemen RI, Feb 15, 2020) . This is all just up to the various benefits of corn and there are many more that we can learn and benefit from the fruit of the seed.